Inovasi Rancangan Kursi Kemudi untuk Mengurangi Tingkat Fatigue pada Pengemudi ketika Proses Pengiriman pada Unit PT Iron Bird Logistics - Muhammad Lutfi Siregar; Darfial Guslan; Afuan Zahradika (Jurnal Studi Inovasi, 2022)
Fatigue is a natural mechanism of the body that shows the body needs rest time to recover stamina that had been used during work, it tends to occur during the transportation process because driving is a job that requires a high level of concentration by requiring fast and precise coordination between the eyes, hands, feet, and brain. Therefore driving is a very high-risk job to get tired. The most common accidents in PT Iron Bird Logistics were caused by high levels of fatigue. Even though the application of UU No. 22 of 2009 about traffic and road transportation which contains the application of rest hours has been implemented properly, it doesn’t change the fatigue as the highest accident factor during the delivery process, therefore the application of the Macro Ergonomic Analysis and Design (MEAD) method was applied to measure body parts that are painful when the driving process and provide ergonomic seat recommendations based on the anthropometric approach of the human body to reduce fatigue levels to reduce accidents and increase performance productivity. The usage of the MEAD method found some parts of the body that were suffering from pain. They are the part of the neck, shoulders, arms including fingers, back, and legs including thighs and knees. The results of the chair design recommendations based on the results of the questionnaire and anthropometric approach are shoulder height (72.18 cm), head height (18.84 cm), popliteal height (40.7 cm), hip width (44.23 cm), thigh thickness (16 cm), and head width (22.61 cm).